Renewable energy consumption, natural resource, urbanization and environmental sustainability in Pakistan - Fatima Farooq; Muhammad Faheem; Asma Nousheen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Energy is an indubitable imperative for economic development, yet it also generates CO2 emissions, which are the leading cause of climate change and environmental deterioration. Renewable energy can stimulate economic growth and can help to achieve economic and environmental sustainability. This paper seeks to investigate the impact of renewable energy consumption, total natural resource rent, urbanization and GDP, on CO2 emissions, ecological footprint (LEF), Methane (LCH4), Nitrogen dioxide (LN2O) and deforestation (LDF) in Pakistan over the period spanning from 1986 to 2021. The present paper employs the autoregressive distributed lag model (ARDL). The empirical evidence revealed that renewable energy and total natural resource rent show negative ramifications on environmental quality, while urbanization and GDP show positive impacts on CO2 emanations. Renewable energy is independent variable and displays different results with different dependent variables. Renewable energy shows a negative association with LEF and LN2O, yet it boosts LCH4 and LDF in the long run.
Keywords: 330; Renewable energy consumption; urbanization; ecological footprint; carbon emissions; deforestation